Methodology for aviation MRO system management decision-making - Korchagin Aleksandr; Deniskin Yury; Pocebneva Irina; Aleksandrovskiy Maxim (E3S Web of Conferences, 2023)
The article considers the main methods for increasing the efficiency of aviation maintenance and repair (MRO) processes organization. A brief overview of these methodologies is presented and their key principles are highlighted. Based on the analysis of existing methodologies, a management decision-making technique based on the Stage-Gate project management technology and simulation modeling methods was proposed. This technique makes it possible to ensure the information availability for the after-sales services organization from other processes in a single information environment and make decisions on the transition to the next gate based on simulation models of aircraft maintenance at various gates.